2010
DOI: 10.3167/nc.2010.050303
|View full text |Cite
|
Sign up to set email alerts
|

Refueling Satoyama Woodland Restoration in Japan: Enhancing Restoration Practice and Experiences through Woodfuel Utilization

Abstract: Urban and peri-urban satoyama woodlands have become focal points of restoration throughout Japan. Prior to the abrupt shift to fossil fuels in the 1950-60s, villages coppiced these woods to produce a sustainable supply of wood fuel, a process that also sustained a dynamic woodland structure rich in biodiversity. Currently, amidst a "satoyama renaissance," thousands of volunteer groups are restoring management to abandoned woods. Yet while volunteers are the main drivers of the satoyama renaissance, volunteer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Data organization and response categorization depended on the type of question. Where appropriate, answers to closed-ended questions were grouped together into discrete categories (e.g., age started foraging was translated to child (0-12), adolescent (13)(14)(15)(16)(17) or adult (18+)). Responses to open-ended questions were written out and compared across all interviews; similar answers were then grouped under common themes, and remaining unique answers were assigned to an "other" category (e.g., hindrances to foraging were grouped into "pollution", "private property", etc.…”
Section: Digital Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Data organization and response categorization depended on the type of question. Where appropriate, answers to closed-ended questions were grouped together into discrete categories (e.g., age started foraging was translated to child (0-12), adolescent (13)(14)(15)(16)(17) or adult (18+)). Responses to open-ended questions were written out and compared across all interviews; similar answers were then grouped under common themes, and remaining unique answers were assigned to an "other" category (e.g., hindrances to foraging were grouped into "pollution", "private property", etc.…”
Section: Digital Databasementioning
confidence: 99%
“…In more recent years, a young, but growing body of research has added considerably to the few pre-existing studies, e.g., [15][16][17]. Cumulatively, the results confirm that urban foraging is an "everyday" (i.e., regular or normal) and surprisingly common practice, both in the Global North [11,18,19] and South [20][21][22]: For example, in a robust household survey study, Robbins et al [23] found that almost 18% of randomly selected residents in four New England states (USA) foraged regularly; more than half of gatherers lived in cities, among them both poorer and wealthier populations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the documentation of people foraging in such diverse settings as several US cities [11,13], Bangalore [19], Delhi [28], Stockholm [29], Edinburgh [23], urban and peri-urban areas in Japan [30], Uganda 45], and towns in South Africa [27,31], there is reason to believe it occurs in cities and towns hitherto not researched. In the studies referred to here, the species harvested included fungi, flowers, berries, medicinal plants, and much more.…”
Section: Emerging Themes Of Urban Foragingmentioning
confidence: 99%
“…Extraction of nutrients is still a common practice, e.g. litter collection in the Satoyama woodlands of Japan [33]. Since all of these practices tend to extract compartments with a relatively high nutrient content in comparison to wood, soil acidification and nutrient depletion was a common threat in Central European forest ecosystems.…”
Section: Biomass From Forestsmentioning
confidence: 99%
“…Standards typically result from genetic regeneration. This multi-aged traditional system supports sustainable production of timber and non-timber forest products, while enhancing ecosystem diversity and wildlife habitat [41], which is also highlighted in the similar Japanese management system of Satoyama [33]. The rotation period for coppice (understorey) is typically 30 years [39,42], hence holding a middle position between planted short rotation woody crops (SRWC) [35] and traditional high forests.…”
Section: Coppice With Standards and High Forest Management In Austriamentioning
confidence: 99%